Linguistic Errors and Descriptive Writing Proficiency in Indonesian EFL Secondary Students - Zuhri Efendi; Sukri Adani (STMIK Indonesia Banda Aceh, 2026)
This study examined linguistic error patterns in the descriptive writing of 50 second language learners, using a mixed-methods approach that combined quantitative error counts with qualitative analysis of coherence and clarity. A total of 253 errors were identified across student responses to prompts such as “banana,” “cat,” and “tiger.” Grammar errors were the most frequent (57 cases, 22.5%), particularly subject–verb agreement and tense misuse, followed by sentence structure (51 cases, 20.2%) and spelling errors (51 cases, 20.2%), with punctuation (50 cases, 19.8%) and capitalization (44 cases, 17.4%) somewhat less common. Correlation analysis revealed grammar (r = –.70), punctuation (r = –.65), and sentence structure (r = –.63) as the strongest predictors of diminished writing quality, while spelling and capitalization played secondary roles. Qualitative evidence confirmed that grammar, punctuation, and structure errors disrupted logical flow and obscured meaning, whereas spelling and capitalization mainly reduced surface polish. These findings, consistent with L2 writing scholarship (Bitchener, 2012; Ellis, 2016), underscore the centrality of grammatical and structural accuracy for coherence in descriptive texts. Pedagogically, the study recommends targeted grammar instruction, punctuation and sentence boundary practice, and genre-based scaffolding, complemented by digital feedback tools and peer review, to enhance students’ ability to produce coherent and reader-friendly descriptive writing.